Alternaria Leaf and Pod Spot of Snap Bean in Florida - Shouan Zhang; Aaron J. Palmateer; Ken Pernezny; Robert T. McMillan, Jr. (EDIS)
Revised! PP-61, a 2-page illustrated fact sheet by Shouan Zhang, Aaron J. Palmateer, Ken Pernezny, and R. T. McMillan, Jr., describes this common and potentially destructive disease of snap bean in Florida — symptoms, cause and disease cycle, and control. Published by the UF Department of Plant Pathology, February 2009.